Defense Mechanism Of Amba Reflected In Laksmi Pamuntjak's The Questions Of Red Novels (2014): A Psychoanalytic Approach - Kahar, Fitrah Abdul, Dr. Abdillah Nugroho, M.Hum (2017)
This research aims to analyze defense mechanism of Amba, reflected on Laksmi Pamuntjak's The Questions of Red novel, the purpose of the research is reveal what is defense mechanism, what kind of defense mechanism and how is defense mechanism reflected in Laksmi Pamuntjak's novel using Psychoanalytic Approach. The type of this research is qualitative research. The researcher took the data from the novel include the narration, monologue, and dialogue. The techniques of collecting the data is using library research, and the technique of the data analysis is using descriptive analysis which comprises procedures: data collecting, data display, and conclusion. Problem statement of the research is: 1) What kind of defense mechanism done by Amba. 2) Why does Amba choose that way to face her problem or anxiety.. 3) The results of defense mechanism chosen by Amba and the result of this research show: 1) Amba's ego defense mechanism leads her to become an independent woman and has a high self confidence. The ego defense mechanism lately can become her friends to through her life, 2) the use of the ego defense mechanism gives strength to Amba to face her problems. Keyword: Defense Mechanism, psychoanalytic approach, The Questions of Red.